2008
DOI: 10.1016/j.immuni.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Independent and Toll-like Receptor-Dependent Antigen-Driven Activation of Autoreactive B Cells

Abstract: SUMMARY On the lupus-prone MRL-lpr/lpr (MRL-lpr) background AM14 rheumatoid factor (RF) B cells are activated, differentiate into plasmablasts, and undergo somatic hypermutation outside of follicles. Using multiple strategies to impair T cells, we found that such AM14 B cell activation did not require T cells, but could be modulated by them. In vitro, the signaling adaptor MyD88 is required for IgG anti-chromatin to stimulate AM14 B cell proliferation when T cells are absent. However the roles of Toll-like rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
201
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(221 citation statements)
references
References 53 publications
17
201
1
1
Order By: Relevance
“…Thus, eTLRs are largely dispensable for humoral responses to foreign protein antigens (Ags), but are, for all practical purposes, necessary for the generation of autoAbs to nucleic acid and nucleic acid-containing material and IgM RF in systemic autoimmunity. These results definitively demonstrate that the eTLRs play a key and essential role in the pathogenesis of lupus in 2 susceptible strains and, in conjunction with previous studies (6,7,12,18,20,33), provide an explanation for the frequent and dominant presence of ANAs in SLE.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, eTLRs are largely dispensable for humoral responses to foreign protein antigens (Ags), but are, for all practical purposes, necessary for the generation of autoAbs to nucleic acid and nucleic acid-containing material and IgM RF in systemic autoimmunity. These results definitively demonstrate that the eTLRs play a key and essential role in the pathogenesis of lupus in 2 susceptible strains and, in conjunction with previous studies (6,7,12,18,20,33), provide an explanation for the frequent and dominant presence of ANAs in SLE.…”
Section: Discussionsupporting
confidence: 86%
“…5). Preventing receptor endocytic transit uncouples the sequential linkage between BCR and TLR engagement necessary to induce B cells to secrete anti-DNA antibodies (12,13,15,19). Thus, our results identify an important functional consequence of the alterations in signaling observed in anergic B cells.…”
Section: Discussionmentioning
confidence: 73%
“…Given the frequency of DNA-binding B cells in the peripheral repertoire, it might be expected that polyclonal anti-DNA antibody secretion would be a usual feature of the immune system (18,19). However, in nonautoimmune prone strains, TLR ligands fail to overcome anergy.…”
mentioning
confidence: 99%
“…4). Granted that this seems counterintuitive, recent publications have unequivocally demonstrated that affinity maturation and class-switching can occur without T cells, albeit the process is more cumbersome (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%